Close up Iranian cinema, past, present and future - Dabashi, Hamid 1951- (Verso, 2001)
This book examines the growing reputation of Iranian cinema, from its origins in the films of Kimiai and Mehrjui, through the work of directors such as Kiraostami, Beyzai and Bani-Etemad, to young film-makers like Bahman Qobadi.
Keywords: Filmkunst; Film; Motion pictures -- Iran; Motion picture producers and directors -- Iran -- Interviews; Iran